ANALISIS POLA PENYEBARAN PENYAKIT DIARE DI KABUPATEN BOGOR - Fitri Mudia Sari (JURNAL GEOGRAFI, 2016)
Diarrheal disease is an endemic disease in Indonesia, meaning it occurs continuously in all regions both in the city and in the village, especially in poor areas. In poor areas are generally diarrhea diseases are considered not as a dangerous disease, so the way healing is not through medical treatment. In fact, diarrhea can cause system disturbances or complications that are very harmful for the sufferer. Some of them are fluid and electrolyte disturbances, hypovolemia shock, various body disorders, and if not handled properly can cause death. Thus it becomes important for the nurse to know more about diarrhea, the negative impact it has, and the handling and prevention of its complications. The objective of this study was to determine the pattern of diarrheal disease spread in Bogor Regency. The method according to the purpose of this research is Ordinary Kriging. To know the distribution of diarrhea disease in Bogor Regency by looking at the result of countour plot. Based on the countour plot, the area that has the highest number of diarrhea sufferers around Barekah and Bojonggenteng villages is marked with White contour color with the range of diarrhea sufferer is 40 - 42 people. Areas with the highest number of diarrheal diseases indicate that the area has a relationship with the number of diarrheal diseases in the surrounding area. Therefore, the area needs to be prioritized in improving water sanitation, counseling to the community and improving health services.